Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Trần Hương Giang

Rút gọn

\(\frac{-1997.1996+1}{-1995.\left(-1997\right)+1996}\) 

 

Trà My
20 tháng 7 2016 lúc 22:48

\(\frac{-1997.1996+1}{-1995.\left(-1997\right)+1996}=\frac{-1997.\left(1995+1\right)+1}{1995.1997+1996}\)

\(=\frac{-1997.1995-1997+1}{1995.1997+1996}\)

\(=\frac{-1997.1995-1996}{1995.1997+1996}\)

\(=\frac{-\left(1997.1995+1996\right)}{1995.1997+1996}\)

\(=-1\)


Các câu hỏi tương tự
Haibara Ail
Xem chi tiết
Lô Thị Cú Mèo
Xem chi tiết
Hạnh Hồng
Xem chi tiết
Đoàn Đức Trung
Xem chi tiết
Lê Cẩm Bình
Xem chi tiết
Vũ lệ Quyên
Xem chi tiết
Vũ Thị Hà Vi
Xem chi tiết
Tường VY
Xem chi tiết
Thu Ngân
Xem chi tiết